Effectiveness of adherence to a preoperative antiplatelet and anticoagulation cessation protocol in cardiac surgery. (21st December 2017) - van Valen, Richard; van Gameren, Menno; Mokhles, Mostafa M; Takkenberg, Johanna J M; ter Horst, Maarten; Hofland, Jan; Bogers, Ad J J C
Abstract: OBJECTIVES: Reduction of blood loss after cardiac surgery remains challenging. The effectiveness of adherence to a protocol on cessation of anticoagulants and platelet-inhibiting medications was investigated together with the influence of protocol violations on blood loss after surgery, use of blood products, surgical re-explorations and 30-day mortality. METHODS: Between 2009 and 2013, data were collected prospectively for all elective cardiac surgery procedures in adult patients ( n  = 1637). Two groups were distinguished: Group 1 adhered to the protocol for cessation or continuation of medication ( n  = 1287, 79%) and Group 2 violated the protocol ( n  = 350, 21%). RESULTS: Median blood loss was 300 ml (interquartile range 175–500 ml). Eighty patients underwent re-exploration due to blood loss (5%). Thirty-day mortality was 2% ( n  = 27). Protocol violation was associated with increased blood loss [median 275 ml (175–475 ml) vs 350 ml (250–612); P  ≤ 0.001] and with increased average use of fresh frozen plasma (226 ml vs 139 ml; P   << 0.00001), red blood cell transfusion (115 ml vs 87 ml; P  = 0.081) and thrombocyte transfusions (52 ml vs 37 ml; P  = 0.0082). The number of re-explorations (4% vs 6%; P  = 0.39) and mortality risk (1% vs 2%; P  = 0.72) did not differ. CONCLUSIONS: Balancing the benefit of continuing platelet inhibitors or anticoagulants versus cessation before surgery remains challenging. Adherence to the protocol will lead to lower blood loss and in a lower consumption of blood products although the decision to go for re-exploration and 30-day mortality does not differ compared with the protocol violation. Stopping medication does not lead to thromboembolic events.